Long‐term trajectories of patients with neck pain and low back pain presenting to chiropractic care: A latent class growth analysis. (4th September 2017) - Ailliet, L.; Rubinstein, S.M.; Hoekstra, T.; van Tulder, M.W.; de Vet, H.C.W.
Abstract: Background: Information on the course of neck pain (NP) and low back pain (LBP) typically relies on data collected at few time intervals during a period of up to 1 year. Methods: In this prospective, multicentre practice‐based cohort study, patients consulting a chiropractor responded weekly for 52 weeks to text messages on their cell phones. Data from 448 patients (153 NP, 295 LBP) who had returned at least one set of answers in the first 26 weeks were used. Outcome measures were pain intensity (VAS) and functional outcome, assessed using four different questions: pain intensity, limitation in activities of daily living (ADL), number of days with pain in the previous week and number of days limited in ADL. Distinct patterns of pain were analysed with quadratic latent class growth analysis. Results: The final model was a 4‐class model for NP and LBP. The 'recovering from mild baseline pain' is most common (76.3% of NP patients/58.3% of LBP patients) followed by the 'recovering from severe baseline pain' class (16.3% NP/29.8% LBP). They follow similar trajectories when considered over a period of 6 months. Pain at baseline, duration of complaints, functional status, limitations in ADL and the score on psychosocial scales were the variables that most contributed to distinguish between groups. Conclusions: Most patients with NP or LBP presenting in chiropractic care show a trajectory of symptoms characterized by persistent or fluctuating pain of low or medium intensity. Only a minority either experience a rapid complete recovery or develop chronic severe pain. Significance: Ninety percentage of patients with neck pain or low back pain presenting to chiropractors have a 30% improvement within 6 weeks and then show a trajectory of symptoms characterized by persistent or fluctuating pain of low or medium intensity. Only a minority either experience a rapid complete recovery or develop chronic severe pain.